A new quantum theory in accordance with Islamic science - Jaafar, Ab. Nasir; Wahiddin, Mohamed Ridza (Springer Singapore, 2016)
Wave-particle duality is one of the many strange phenomena observed in the quantum world that desperately requires a new theory. Such a theory is proposed herein through a metaphysical approach based on the Qur’an and the principles of Islamic science, supplemented by philosophical rational arguments. Interpreting relevant Qur’anic verses, together with the pairing concept and the one-to-one correspondence principle, manages to facilitate some detailed explanations regarding the wave-particle duality of an electron. Scientific analysis indicates an electron can consist of both a unit electrical charge and a permanent magnet, which all reflects on its wave-particle duality behaviour as per experimental observations. Though physicists are currently only considering the existence of the induced magnetic field, the presence of which is due to the spin of the electron, the new theory postulates that a permanent magnetic field is additionally present. Furthermore, the electrical charge and the permanent magnetism could be considered as potential energy, which is also believed to be possibly the zero point energy that has been observed to exist, but has yet to be properly explained. Based on this new theory, a mathematical equation has been derived to calculate the postulated potential energy of an electron. Islamic science in this case appears to have demonstrated its significance in proposing a new perspective in the exploration of the mysterious quantum world.